Sample disturbances due to removal of confining pressure in laminated clay. Issue 5 (1st October 2019) - Moore, L.; Pandey, P.; Sivakumar, V.; Donohue, S.; Mackinnon, P.; Doherty, C.
Abstract : Sample disturbances in laminated soils may be caused by several factors including water movement between the clay and sand layers upon removal of overburden pressures. The research reported in this article examines the impact of this water movement on various geotechnical parameters. Samples of kaolin with laminations were formed and subjected to isotropic consolidation and subsequently sheared under undrained conditions. Further tests were carried out in which the samples were isotropically unloaded after consolidation and isotropically reloaded under undrained conditions and this was then followed by undrained shearing. Tests were also carried out to examine the impact of unloading/reloading on the yield stress and small strain stiffness (Gmax ). The results have shown that the isotropic unloading/reloading process under undrained conditions leads to reduction in undrained shear strength, small strain stiffness (Gmax ) and yield stresses. Comparative tests carried out on unlaminated samples showed that the unloading/reloading process has a marginal impact on the above mentioned geotechnical properties.